A revision of Zoosetha Mulsant & Rey and Poromniusa Gangl-bauer. II. A new species from Spain and additional records (Coleoptera: Staphylinidae: Aleocharinae) - Assing, Volker (Zootaxa, 2003)
Zoosetha wunderlei sp. n. (Spain: Sierra de Segura), the nineth species of the genus, is described, illustrated, and distinguished from its congeners. Additional records of other species of Zoosetha Mulsant & Rey and of Poromniusa Ganglbauer are presented. The distributions of Zoosetha wunderlei, Z. inconspicua (Erichson), Z. incisa Assing, Poromniusa procidua (Erichson), and P. crassa (Eppelsheim) are mapped.